2014
DOI: 10.46568/pjgs.v9i1.244
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange-Marriage System, Traditional Gender Roles And Obscured Transformations In A Community Of Pakistan: The Interplay Between Structure, Agency And Social Change

Abstract: This article deals with the traditional and changing gender roles and relationships in the exchange-marriage system that exists in south Punjab, Pakistan. It examines the structural roles and an individual’s independent choices. In-depth interviews were conducted with twenty-four families who have utilized the system of exchange. In this research the guidelines of the Grounded Theory Method (GTM) in order to collect and analyse the data. The study found that pre-determined, structured roles were more influenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Participants living in the nuclear family system scored higher on relationship satisfaction and commitment level whereas those living in the joint family system scored higher on the quality of alternatives. In collectivist societies, relationships are bound to be influenced by social and situational constraints, gender roles, as well as the current social context of a couple's life (VanderDrift et al, 2013;Zaman & Shehzad, 2018). Current study findings are in line with the study of Ayub et al (2022) as they concluded that men are more satisfied in a relationship than their female counterparts but when it comes to bonding and emotional connection with partners, women scored slightly better than their spouses.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Participants living in the nuclear family system scored higher on relationship satisfaction and commitment level whereas those living in the joint family system scored higher on the quality of alternatives. In collectivist societies, relationships are bound to be influenced by social and situational constraints, gender roles, as well as the current social context of a couple's life (VanderDrift et al, 2013;Zaman & Shehzad, 2018). Current study findings are in line with the study of Ayub et al (2022) as they concluded that men are more satisfied in a relationship than their female counterparts but when it comes to bonding and emotional connection with partners, women scored slightly better than their spouses.…”
Section: Discussionsupporting
confidence: 84%
“…Current study findings are in line with the study of Ayub et al (2022) as they concluded that men are more satisfied in a relationship than their female counterparts but when it comes to bonding and emotional connection with partners, women scored slightly better than their spouses. Moreover, based on cultural inhibition and societal pressure women do not consider any available alternative of relationships whereas men are always considered to be the one attracted towards better option in relationship that is also instigated by religious and cultural acceptance of more female partners as male (Aman et al, 2019;Hayee & Kamal, 2022;Zaman & Shehzad, 2018). This supports the cultural notion that irrespective of whatever people are facing in a relationship they will ultimately report it to be satisfying as the social disapproval of ending such a relationship is higher (Bilal & Rasool, 2020;Qadir et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of marriages is used to control and maintain a balance of power between families and the couples (Naveed & Butt, 2015: 167). The men's behaviour is conditioned through good or abusive treatment extended to his blood relative bride involved in exchange and living in other party's home (Jacoby & Mansuri, 2010, 1806Zaman 2013;Zaman, Zakar, & Sharif 2014). Therefore, it is considered as a double edged sword that cuts both ways (Bhutta et al 2015: 167;Jacoby & Mansuri, 2010, 1813.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is in Pakistan's South Punjab that traditional gender roles and relations have changed in the marriage system, which has changed roles. Predefined, structured roles are more influential and essential than individual choices (Zaman et al, 2013;Thakur, 2019).…”
Section: Introductionmentioning
confidence: 99%